Answers

2016-01-12T23:55:02+05:30
siiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiiimple
///////////////////////////////////////////////////////////
x2 - r3x - 1x + r3 =0
=> x(x-r3) -1 (x-r3)=0
=> (x-r3)(x-1)=0
=> x=r3 or x=1
............................................................
r====> square root
2 4 2
u have learnt about
quadratic formula
x= -b +- b2 - 4ac / 2a
simply
a=1
b=5
c= -(a2+a-6)= -a2-a+6
..................
putting values
.........................
x= (a-2) or x= -(a+3)
Thnk uy friend btw what is your name
doesnt matter
leave it
Ok
2016-01-13T11:33:18+05:30
Take x² - (√3 +1)x + √3 = 0
⇒ x² - (√3x + x) + √3 = 0
⇒ x² - √3x - x +√3 = 0
⇒ x(x-√3) - 1(x-√3) = 0
⇒ (x-√3)(x-1) = 0
⇒ x-√3 = 0       or   x-1 = 0
⇒ x =√3           or   x =1
∴ x =√3 or 1
0